Watching Waleed: celebrity authenticity, Australian national identity, and the ideological work of The Project. Issue 3 (3rd July 2017) - D'Cruz, Glenn
ABSTRACT: Waleed Aly is the most visible Australian public intellectual from a non-Anglo-Australian background. In 2016, Aly won the most coveted prize in Australian television: The Gold Logie. He was voted the most popular celebrity on Australian television primarily on the basis of his role as the co-host of the news/entertainment panel show The Project . This article interrogates a selection of Aly's notable media appearances with a focus on his role as the co-host of The Project, a popular current affairs show on Australian television, in order to unpack the complex relationship between his celebrity status and his standing as a public intellectual, which bestows Aly with a symbolic, if not literal, mandate of authority and authenticity. More specifically, the article analyses a series of complex performative acts that align Aly's public persona with a normative conception of Australian national identity. These acts involve two fundamental co-implicated operations. The first is a conscious self-presentation best thought of in dramaturgical terms. The second is best apprehended with reference to those discursive and institutional factors that make a place ready for us in the order of things. Finally, the article presents an account of the ideological work performed by Aly's 'authentic' celebrity persona.